Pengaruh Video Tutorial Terhadap Kreativitas Siswa dalam Membuat Bendera Hias Pembelajaran Seni Rupa - Fajar, Farid Fadhilah; Tarmizi, Pebrian; Noperman, Feri (JURIDIKDAS, 2024)
The purpose of this study is to ascertain how students' inventiveness in creating ornamental flags during fine arts instruction at SDN Gugus XIX, Bengkulu City, is impacted by video tutorials. This kind of study uses a quasi-experimental design, matching just pretest-posttest control groups, using quantitative methods. SDN Gugus was the research population. Cluster Random Sampling is used in the sampling method. The tool that was employed is the assessment rubric used during the pretest and posttest. Data analysis techniques include quantitative analysis with descriptive statistics, prerequisite test analysis as well as t-test inferential analysis. Considering the outcomes of inferential analysis, the value of tcount (3.494) > ttable (2006). Sig value. (2-tailed) is (0.001) < (0.05). The average creativity score of experimental class students (65.56) and control class (62.41). The difference in scores occurred due to different treatment between the control class and the experimental class during learningWithin the trial class the learning was given treatment using video tutorials, whereas the learning in the control group used PPT media. In light of this, it is known that there is an influence of video tutorials on students' creativity in making decorative flags in fine arts learning at SDN Gugus XIX, Bengkulu City.